Fingerprint Image Enhancement Algorithms for Identification in an Electoral Process - Olatubosun, Olabode; O.A, Fasoranbaku (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Electoral process in many developing nations is characterized with fraud and failure as a result of inefficient and effective system of voter’s register and voting system. This usually leads to crises. This paper presents enhancement algorithms of Denoising fingerprint images using Moving Average Filter, the Segmentation of Fingerprint using Chen algorithm, Gradient-Based Local Ridge Orientation, Binarization using Otsu Algorithm, Thinning of Fingerprint Image using the linear interactive approach and Minutiae Extraction using the minutiae location and minutiae angles for the purpose of verification and Identification in electoral process. The input to the system is a Gray-scale Fingerprint image of electorate and it detailed information while the Output is a Verified and enrolled fingerprint image with matching score and details of electorates’ information store as Template using the Matlab 2013a.